3(6-1)=11p-45

Simple and best practice solution for 3(6-1)=11p-45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6-1)=11p-45 equation:


Simplifying
3(6 + -1) = 11p + -45

Combine like terms: 6 + -1 = 5
3(5) = 11p + -45

Multiply 3 * 5
15 = 11p + -45

Reorder the terms:
15 = -45 + 11p

Solving
15 = -45 + 11p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-11p' to each side of the equation.
15 + -11p = -45 + 11p + -11p

Combine like terms: 11p + -11p = 0
15 + -11p = -45 + 0
15 + -11p = -45

Add '-15' to each side of the equation.
15 + -15 + -11p = -45 + -15

Combine like terms: 15 + -15 = 0
0 + -11p = -45 + -15
-11p = -45 + -15

Combine like terms: -45 + -15 = -60
-11p = -60

Divide each side by '-11'.
p = 5.454545455

Simplifying
p = 5.454545455

See similar equations:

| A^2(b-1)-25(b-1)= | | 2(-5)+7(-25)-9(-5)+21(-50)+5(-5)= | | (k+1)x^2+(k+1)y^2+2kx+2ky+2y+4k+3=0 | | .25x-5+171=x | | 20/12=50/x | | 3(-5)(2)+6(-5)+-5(3(2)-6)= | | 2x+3x+(2+6)=8 | | 7x-2=4x-2 | | y=-2x+16x-24 | | ln(5x-2)-ln(x+3)=2 | | 5(2+p)=17.5 | | 5x+45-89=-90+41 | | 3+2p=7 | | -5(2(2)+7)+2(9)+5(-5)= | | 5(z-1)-20=0 | | Y=2ln(3x-1)-2 | | -10x^2-6x-12=0 | | -4=-8x+2 | | 9(4(-25)-3)= | | ln(x-6)=24 | | 90t=450t | | 9t^2-54=0 | | -24r+6= | | 9(-5)(2)+3(-25)-7(4)+8(-5)(2)-12= | | Y=-8sin(7x) | | 8=2d-12 | | -7x-y+z=-12 | | x-9=.75x | | (5x+5)+(-6x+8)= | | x^2+y^2+18x+12y=11 | | 8b+3=5b+7 | | 3(3x-7)=81(12x-3x) |

Equations solver categories